The Middle Palaeolithic of the Nejd, Saudi Arabia. (3rd March 2016) - Groucutt, Huw S.; Breeze, Paul; Drake, Nick A.; Jennings, Richard; Parton, Ash; White, Tom; Shipton, Ceri; Clark-Balzan, Laine; Al-Omari, Abdulaziz; Cuthbertson, Patrick; Wedage, Oshan M. C.; Bernal, Marco A.; et al.
Abstract : The Pleistocene archaeological record of the Arabian Peninsula is increasingly recognized as being of great importance for resolving some of the major debates in hominin evolutionary studies. Though there has been an acceleration in the rate of fieldwork and discovery of archaeological sites in recent years, little is known about hominin occupations in the Pleistocene over vast areas of Arabia. Here we report on the identification of five new Middle Palaeolithic sites from the Nejd of central Arabia and the southern margins of the Nefud Desert to the north. The importance of these sites centers on their diversity in terms of landscape positions, raw materials used for lithic manufacture, and core reduction methods. Our findings indicate multiple hominin dispersals into Arabia and complex subsequent patterns of behavior and demography.